A Makerspace Network as Part of a Regional Innovation Ecosystem, the Case of Emilia-Romagna - Andrea Cattabriga (European Journal of Creative Practices in Cities and Landscapes, 2020)
Makerspaces and their various declinations are a widespread initiative of workshops that offer open access to digital and traditional production equipment, with the aim of democratizing access to technologies and supporting bottom-up innovation. They are recognized as a new form of ‘third places’ in a contemporary perspective. As the number of such places grows along with their active communities, business models, contamination projects with universities, companies, and civil society, many researchers have explored the ability of makerspaces to serve as innovation facilitators. Over the last few years, networks and coalitions of makerspaces have started to pop-up with a range of objectives, such as the advocacy and coordination of territorial or project-oriented coalitions; however, they remain largely unanalyzed and undocumented. The paper explores the phenomenon of these networks, drawing on a case study that describes the development of a makerspace regional network in Northern Italy, providing insights concerning its impact on both relationships at a local level and on the acceptance of third places within a regional innovation system, contributing to opening a new field of discussion about the potential of such networked organizations.